THE EFFECTIVENESS OF QUESTION ANSWER RELATIONSHIP (QAR) STRATEGY IN TEACHING READING COMPREHENSION - Yunita Dwi Wikandari (Jurnal Bahastra, 2019)
As a language skill, reading plays an important role because reading has become part of our daily lives. Reading is also an important way to improve pupils apos; common language skills in English. However, reading is not easy because when students read, they also need to understand what is being read. One way to help students understand what they read is to use a question-and-answer strategy (QAR). The aim of the study was to obtain empirical evidence of the effectiveness of the QAR strategy in teaching an 11th grade student SMAN 1 Bangsal in the 2016-2017 academic year. The design of the study was quasi-experimental, using design only for two groups after testing, which passed through two classes: the pilot group and the control group. After the tests were performed, the post-test showed that the average score obtained by the experimental class was 81.12 and the control class was 72.75, while both classes were equal. It was proven by the result of homogeneity test, that Fh was lowest than Ftable (1.32 1.89). From the result of t-test, it was obtained the tvalue was 9.05 higher than ttable (9.05 1.89). It means that H2 is accepted and the Ho is rejected. So, there is a significant effect of using QAR strategy on students reading comprehension ability.